Associations of mechanical power, ventilatory ratio, and other respiratory indices with mortality in patients with acute respiratory distress syndrome undergoing pressure-controlled mechanical ventilation - Kim, Tae Wan; Chung, Chi Ryang; Nam, Miryeo; Ko, Ryoung-Eun; Suh, Gee Young (Frontiers in Medicine, 2025)
BackgroundMechanical power (MP) and ventilatory ratio (VR) are crucial metrics in the management of acute respiratory distress syndrome (ARDS). This study aimed to evaluate the impact of these factors on ICU mortality in patients with ARDS undergoing pressure-controlled ventilation.MethodsIn this retrospective study, we included 600 adult patients with ARDS who required mechanical ventilation for > 48 h between March 2018 and February 2021 in a tertiary referral hospital in Korea. The MP was calculated using Becher's simplified equation, and the VR was determined using standard formulas. The ventilatory parameters were measured hourly during the first 12 h of ventilation. Clinical characteristics, ventilator settings, and outcomes were compared between the survivors and non-survivors. Multiple logistic regression models were used to assess the predictive performance of the respiratory and mechanical ventilation parameters for ICU mortality.ResultsOf the 600 patients, 61.5% (n = 369) survived to hospital discharge. Non-survivors had higher rates of chronic liver disease, hematologic malignancies, and solid tumors. The survivors demonstrated lower respiratory rates (21 vs. 22 breaths/min, p < 0.001), tidal volumes (491 vs. 445 mL, p = 0.048), and peak pressures (22.0 vs. 24.3 cm H2O, p < 0.001). Significant differences were observed in driving pressure (15.0 vs. 16.0 cm H2O, p = 0.001), MP (18.8 vs. 21.8 J/min, p < 0.001), LTCdyn-MP (7,371 vs. 8,780 cm H2O/min, p < 0.001), and power index (5,429 vs. 6,386 cm H2O/min, p = 0.005) between survivors and non-survivors. In adjusted models, MP (OR 1.03, 95% CI 1.01–1.05, p = 0.006), VR (OR 1.39, 95% CI 1.02–1.92, p = 0.040), and PBW-adjusted MP (OR 1.02, 95% CI 1.00–1.03, p = 0.009) were significant predictors of ICU mortality.ConclusionOur findings indicate that MP and VR were independently associated with ICU mortality in patients with ARDS undergoing pressure-controlled ventilation.